The Effect of Per Capita Income and the Agricultural Sector on Goods and Services Tax Receipts with Economic Growth as Moderation in BRICS Countries - Kusuma, Michael; Wijaya, Suparna (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
The purpose of this research is to analyze the effect of per capita income and the agricultural sector on goods and services tax revenues with economic growth as the moderation in the combined economy countries, BRICS (Brazil, Russia, India, China, and South Africa). The variables used in this study are the ratio of goods and services tax revenue, per capita income, the contribution of the agricultural sector, and the percentage of economic growth. The data source comes from the World Bank Data for the period 2010 to 2018. The research method used is quantitative using panel data and multiple linear regression analysis techniques. The Random Effect Model is a model selected based on panel model testing. Simultaneously, all variables have a significant effect on goods and services tax revenues. Partially, per capita income, agricultural sector, and economic growth have a significant negative effect on goods and services tax revenues. This research is expected to provide insight to the governments of the BRICS countries in making policies to optimize goods and services tax revenues through per capita income, the agricultural sector, and economic growth.